Creating Tourist Loyalty through Destination Branding for an Excellent Tourism Destination - SEPTARINA, Linda; ZURIANA, Zuriana; BESTI, Lilyana (Journal of Environmental Management and Tourism, 2022)
The objective of this research was to create the loyalty of tourists toward the excellent destination's branding. Some problems such as lack of facilities and weak characteristics of destination attractions less tourist arrival. The research is causative, using 95.000 samples of the tourist taken from tourists’ arrival in 2018-2020. Using path analysis, we also found relationships between loyalty and excellent tourist destination branding due to some externalities of destination attraction such as accessibility, amenities, and attraction. Those show that the destination has weak characteristics to become an excellent branding.